Pelatihan dan Penyuluhan Upaya Peningkatan Penjualan Produk UMKM Menggunakan Tiktok Ads - Erislan (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
In today's digital world, social media platforms have become the hub of activity for millions of users worldwide, sharing photos, videos, interacting with friends, and even shopping online through e-commerce which is now integrated with social media. The use of social media has grown and evolved over the past two decades. With the COVID-19 pandemic, individuals have had to engage in activities remotely using the internet, leading to a significant increase in social media consumption. The positive impact of social media includes easy long-distance communication, real-time information access, and much more. Moreover, social media seems to be a space for interaction for all internet users. The latest phenomenon is TikTok Shop. TikTok, originally a social media platform, has evolved into an e-commerce platform that allows users to directly purchase products through the app, introducing a new category known as social commerce. TikTok's emergence has shaken the online world with its concept of live video sharing, quickly becoming very popular, especially among the younger generation. TikTok's success in becoming a social commerce platform is one of the biggest success stories in the history of social media. Through TikTok Shop, brands, merchants, and users can interact and showcase products through short videos on this platform, offering a more personal and interactive shopping experience. Even more, e-commerce merging with social media has prompted the government to revise Minister of Trade Regulation No. 50 of 2020 concerning Licensing of Business, Advertising, Development, and Supervision of Business Actors in Electronic Trading (PPMSE). This revision is believed to provide a form of protection for SMEs.